Analysis of breast cancer-associated glycosphingolipids using electrospray ionization-linear ion trap quadrupole mass spectrometry. (30th January 2015) - Zhu, Tingting; Xu, Longjiang; Xu, Xiukun; Wang, Zheng; Zhu, Jian; Xie, Qing; Zhang, Biyan; Wang, Yanping; Ju, Linling; He, Yun; Ye, Xinshan; Zhou, Dapeng; et al.
Graphical abstract: Highlights: LTQ-ESI-MS has developed as an efficient method to determine the cancer-associated GSLs. The structure of fucosyl-lactoceramide overexpressed in breast cancer patients is Fucα1 → 2 Galβ1 → 4Glcβ1 → 1Cer. Terminal α1, 2 fucose is a characteristic of breast cancer-associated GSLs. Profiling of cancer-associated GSLs contributes to diagnosis and therapy of human carcinomas. Abstract: Abnormal glycosphingolipids (GSLs) are expressed in many human tumors. These tumor-associated GSLs may have important roles in tumor progression. However, they are hard to be detected because of their low concentration and the limited availability of antibodies and lectins that recognize them. Thus, mass spectrometry is an effective method to analyze GSLs with high sensitivity. Here, we use electrospray ionization-linear ion trap quadrupole mass spectrometry (ESI-LTQ-MS) and liquid chromatography/electrospray ionization tandem mass spectrometry (LC/ESI-MS/MS) to determine the structure of a certain GSL in human breast cancer tissue. To obtain the breast cancer-associated GSLs, we applied relative abundance contrast of GSLs and signal-to-noise ratio (SNR) analyses. We also used α1, 2 fucosidase and fucosyltransferases as tools in the structural analysis. Based on this analysis, we identified the ion with m / z 1184 molecular ion as fucosyl-lactoceramide (Fuc-LacCer) with a C16 fatty acid ceramide. Quantitative analysis of GSLs revealed both Fuc-LacCer and Globo-H increased in breast cancer tissues. However, these two breast cancer-associated GSLs had different roles. The results of SNR analysis suggested the abnormal Fuc-LacCer is specific to breast cancer. The GSL profiling of breast cancer cells showed fucosyltransferase 1 contributed to the biosynthesis of Globo-H and Fuc-LacCer. In conclusion, MS analysis identified an accumulation of Fuc-LacCer in breast cancer tissue. Our findings provide GSL profiles of human breast cancer and develop an MS method for the study of cancer-associated GSLs.